2021
DOI: 10.2106/jbjs.21.00018
|View full text |Cite
|
Sign up to set email alerts
|

Early Sport Specialization

Abstract: Early sport specialization has been recognized as a potential factor in the relationship between physical activity and health since the early 1970s.There is no universally agreed-upon terminology or definition for early sport specialization, but early sport specialization typically encompasses preteen athletes who play 1 sport competitively throughout the year or play on several teams within 1 season, leading to intensive participation without variation in physical activity.There is a limited number of compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A recent meta-analysis concluded that highly specialized youth were more likely to report a history of injury associated with sport participation. 3 Subsequent reviews agree with evidence of increased risk of overuse injury 10 and lower extremity injury specifically. 11 However, these reviews acknowledge limitations in the evidence, including a lack of adjustment for confounding due to training and competition volume and a lack of studies specifically investigating early specialization.…”
Section: Introductionmentioning
confidence: 82%
“…A recent meta-analysis concluded that highly specialized youth were more likely to report a history of injury associated with sport participation. 3 Subsequent reviews agree with evidence of increased risk of overuse injury 10 and lower extremity injury specifically. 11 However, these reviews acknowledge limitations in the evidence, including a lack of adjustment for confounding due to training and competition volume and a lack of studies specifically investigating early specialization.…”
Section: Introductionmentioning
confidence: 82%
“…There is no broadly accepted definition of “specialization.” Is specialization a subjective self-defined state where the athlete considers themselves to be specializing, but still plays other sports, or is sport specialization an objective state in which the individual stops playing all other sports? 11 , 12 Conversely participation in a single sport does not necessarily imply specialization.…”
Section: Introductionmentioning
confidence: 99%